Monitoring and Controlling Electric Power Stations Using GSM Network - Ismail, Goran; A. Mubdir, Bilal; Majeed, Asso; Al-Hindawi, Asaad Mubdir Jassim (Kurdistan Journal of Applied Research, 2019)
This paper introduces a system design for monitoring and controls the components of power generation station and substation with help of existing communication link based on GSM network. In this design, a selected Programmable Logic Controller (PLC) connected to the fields that needed to be monitored and continuously read changes in measurements of electrical parameters like voltage, current, bus bar circuit breakers…..etc.. These parameters have been monitored by PLC, on the base of conditions that PLC is programmed. PLC generates a text message and forward to other side; control center or mobile phone of engineer and technicians; who are responsible of monitoring. At control center, another GSM modem which has capability to connect with personal computer, receives that text massage using SMS and executes it. Software written with Vb.Net, works as Human Machine Interface (HMI) for this purpose. The system performance is acceptable in terms of errors in readings and time delay. The percentage error for the current is about 1%, and for the voltage is about 0.2%. The delivery time to receive new analog and digital inputs data is about 14.125 seconds, while the control of the circuit done after 4.68 seconds.